Social media marketing adoption: Is it important for homestay operators in Malaysia? / Noraihan Mohamad - Mohamad, Noraihan (UiTM Press, 2024)
Social media marketing has become a vital tool for businesses to promote their products and services, yet its adoption among SMEs in Malaysia, particularly homestay operators, remains limited. This study examines the factors affecting the adoption of social media marketing by homestay operators in Malaysia. Based on a cross-sectional research design, data were collected from 208 operators in Selangor, Negeri Sembilan, Melaka, and Johor via a self-administered questionnaire. Structural Equation Modelling identified that customer pressure and preference, as well as competitive pressure, significantly influence the adoption of social media marketing. In contrast, perceived cost and digital skills were found to have a lesser impact. These results offer valuable insights for policymakers to understand adoption trends among Malaysian SMEs. Social media marketing presents a costeffective strategy for SMEs, providing extensive connectivity and interaction capabilities. The study underscores SMEs’ need to embrace new technologies to enhance their marketing strategies and improve business outcomes.